Measuring Perceived Service Quality In The Hotel Industry: A Study On Luxury Hotels In Malaysia - Abaeian, Vahideh (2011)
The present research intends to study the expectations and perceptions of luxury hotels guests who come from either advanced or emerging/developing economies to Malaysia. The research found that the hotel customers\' perceptions of the hotel industry\'s service quality were higher than their expectations. Moreover, the difference between male and female guests from advanced and emerging/developing economies was significant in terms of their preferences of service quality dimensions.